2022
DOI: 10.1186/s13256-021-03227-0
|View full text |Cite|
|
Sign up to set email alerts
|

Transitory ischemic attack associated with a rare fenestration of the cervical segment of the internal carotid artery: a case report

Abstract: Background Fenestration of the cervical segment of the internal carotid artery is a very rare finding, and its origin is still not fully understood. Explanations of its genesis range from dissections leading to the fenestration to the more common interpretation as a developmental vascular variant. However, most reported cases were symptomatic and presented with dissections, where even endovascular treatment of the fenestration of the cervical segment of the internal carotid artery became necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The latter does not negate the fact that fcICA on a ground of FMD bears a considerable risk of dissection and should be closely monitored. Since fcICA is exceptionally rare there are no established treatment recommendations (4,7).…”
Section: Discussionmentioning
confidence: 99%
“…The latter does not negate the fact that fcICA on a ground of FMD bears a considerable risk of dissection and should be closely monitored. Since fcICA is exceptionally rare there are no established treatment recommendations (4,7).…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported errors in the contributing author names. The given name and family name were erroneously transposed.…”
Section: Correction To: J Med Case Reports (2022) 16:13 Htt...mentioning
confidence: 99%